Metaphysics of Progress in the Russian Religious Philosophy - Vladimir Borisovich Aleksandrov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article, views of the Russian philosophers on progress are considered. It is noted that a basic point of reflections of a number of domestic thinkers on the matter is the criticism of the «eudemonistic» approach consisting in understanding of progress as increases of happiness of the person and improvement of conditions of his life. They treat this approach as a projection of a way of thinking peculiar to political economy according to which driving motive of economic development is increase of requirements. Neither the political economy nor other concrete sciences cannot define in their opinion criteria of satisfaction of requirements. The Russian philosophers also criticize the concept of progress, which gained distribution in Marxism as increases of opportunities for development of the personality. In their opinion, its insolvency is in understanding of the personality not based on deep metaphysics, as in the German classical philosophy, in particular in Hegel’s philosophy, but reduced to its understanding as an epiphenomenon of the public relations. Addressing to idea of progress, the science inevitably mixes historical progress and progress of a civilization that conducts to loss of a moral perspective of historical progress and, as result, to peculiar «progress religion». For the Russian philosophy progress is, first, a moral task. The metaphysics of progress in the Russian philosophy is based on distinction of two types of thinking: chiliastic - connected with belief in a thousand-year kingdom with triumph of goodness (an example of such thinking is social-ism), and eschatological taking out the history purpose out of its limits. In the deepest meaning progress is the eschatological idea assuming statement of history in the face of transcendence. However, it does not mean that it indicates the need of «desecration of real life», as, however, and acceptance of unjustified optimism. The history for the Russian thinkers is an accruing contradiction between the good and evil. For this reason for the Russian thinkers, tragic vision of history is peculiar. Progress of a civilization is possible in history, but an internal result of history is tragedy. In the article is noted that the Russian thinkers revealed deep metaphysics content of the idea of progress, having separated approach of positive science from philosophical sense of this problem. Having concentrated the attention on a human aspect of progress, they brought a moral perspective of idea of progress to the forefront. The Russian philosophers showed that the image of the purpose of history has deep metaphysical sense and cannot be expressed in the terms defining life of the person in the terrestrial world.